Peningkatan Layanan Keuangan Sekolah dengan Aplikasi Cashless Payment (Studi Kasus SMK Pariwisata Telkom Bandung) - Bayu Rima Aditya; Aldilla Iradianty; , Inne Gartina; Sri Rahayu; Guntur Prabawa Kusuma; Dedy Rahman Wijaya; Siska Komala Sari (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
SMK Pariwisata Telkom Bandung is a school that is under the auspices of the Yayasan Pendidikan Telkom and is a partner in this community service program. The problem faced by partners is the limited level of knowledge and skills of schools in using information and communication technology (ICT) which causes a lack of innovation implemented in school, especially in the financial function. The solution offered in the program is to provide training and assistance in terms of digitalization school financial services based on cashless payment to support innovation in school financial services. The results of participant feedback have shown that the program can positively provide digital literacy education related to the recent financial technology. Therefore, this program contributes to strengthening and improving the ability to manage school financial services. In addition, this community service activity also produces an appropriate technology in the form of a cashless payment-based school finance application.